2005
DOI: 10.1111/j.1398-9995.2005.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

A differing pattern of association between dietary fish and allergen‐specific subgroups of atopy

Abstract: We have demonstrated a differential effect of fish intake for sensitization to different aeroallergens. This may be due to the different timing of allergen exposure during early life. Further investigation of the causes of atopic disease should take into account allergen-specific subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
0
22
0
2
Order By: Relevance
“…This can result in increased production of arachidonic acid and prostaglandin E 2 with a consequent increase in the likelihood of atopic T-helper (Th) cell type 2 sensitisation, asthma and atopic disease [2]. Several studies have reported beneficial associations of dietary fish intake [5,6,8,22,23,[27][28][29] or harmful associations of margarine and vegetable oil intake [4,9,23,27,29] with asthma and atopic disease in children, whereas other studies did not find effects of n-3 PUFAs [4,7,20] or n-6-rich foods [18]. In the present study, increased fish consumption at early age appeared to be protective for sensitisation to inhaled allergens and BHR, but seemed to increase the risk of sensitisation to food allergens at 8 yrs of age.…”
Section: Discussionmentioning
confidence: 99%
“…This can result in increased production of arachidonic acid and prostaglandin E 2 with a consequent increase in the likelihood of atopic T-helper (Th) cell type 2 sensitisation, asthma and atopic disease [2]. Several studies have reported beneficial associations of dietary fish intake [5,6,8,22,23,[27][28][29] or harmful associations of margarine and vegetable oil intake [4,9,23,27,29] with asthma and atopic disease in children, whereas other studies did not find effects of n-3 PUFAs [4,7,20] or n-6-rich foods [18]. In the present study, increased fish consumption at early age appeared to be protective for sensitisation to inhaled allergens and BHR, but seemed to increase the risk of sensitisation to food allergens at 8 yrs of age.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies observed a beneficial effect of fish intake during infancy/ childhood and atopic outcomes in those infants/children [36][37][38][39][40][41][42][43][44]. Two of the studies observed a negative effect of fish intake on childhood atopy [45,46], and three studies observed no associations [47][48][49].…”
Section: Pufas Eicosanoids Inflammatory Processes and Atopymentioning
confidence: 97%
“…Of the studies that found a beneficial association between fish intake during infancy/childhood and atopic outcomes, three were prospective cohort [38,41,49], two were case-control [36,37], and four were cross-sectional [39,40,42,43]. The age range of children taking part in these studies was between 1 and 18 years (at the time point that outcomes were measured).…”
Section: Pufas Eicosanoids Inflammatory Processes and Atopymentioning
confidence: 98%
“…Nevertheless, there are different and partly inconsistent results concerning the n-3 hypothesis. Some studies could find significant associations between PUFAs in the diet, allergic sensitisation and allergic symptoms [4,8,9,11,21] , but other studies found no such effect [22][23][24][25][26][27][28] . Although the n-3 hypothesis is biologically plausible, it has not been confirmed by many epidemiological studies [29] .…”
Section: Introductionmentioning
confidence: 99%